Cell specific expression of peroxiredoxins in human lung and pulmonary sarcoidosis. Issue 2 (1st February 2002) - Kinnula, V L; Lehtonen, S; Kaarteenaho-Wiik, R; Lakari, E; Pääkkö, P; Kang, S W; Rhee, S G; Soini, Y
Abstract : Background: Six proteins of the peroxiredoxin (Prx) family have recently been characterised which have the capacity to decompose hydrogen peroxide in vivo and in vitro. These proteins may have an important role in the protection of human lung against endogenous and exogenous oxidant stress. However, the expression and distribution of these proteins in healthy human lung and diseased lung tissue is unknown. Methods: The cell specific expression of Prxs in healthy lung tissue from four non-smokers and in parenchymal tissue from 10 subjects with pulmonary sarcoidosis was investigated by immunohistochemistry, and expression of these proteins in various cultured lung cells and cells of bronchoalveolar lavage (BAL) fluid of controls and patients with sarcoidosis was assessed by Western blot analysis. Results: All six Prxs could be synthesised in cultured human lung cells. The bronchial epithelium showed moderate to high expression of Prxs I, III, V and VI, the alveolar epithelium expressed mainly Prxs V and VI, and alveolar macrophages expressed mainly Prxs I and III. Granulomas of subjects with sarcoidosis expressed mainly Prxs I and III. Samples of BAL fluid from controls and from subjects with sarcoidosis had very similar findings, except that Prxs II and III had a tendency for increased immunoreactivity in sarcoidosis tissue. Conclusions: Prxs I, III, V, and VI, in particular, have prominent and cell specific expression in human lung tissue. High expression of Prxs I and III in granulomas and alveolar macrophages of sarcoidosis parenchyma may have a significant effect on the oxidant burden and the progression of lung injury in this disease.